Prospective Radiographic Assessment of Intraoperative Range of Motion with Total Ankle Replacement. Issue 1 (January 2022) - Gagné, Oliver; Bitar, Rogerio C.; Kim, Jaeyoung; Caolo, Kristin C.; Saito, Guilherme H.; Cody, Elizabeth; Deland, Jonathan T.; Ellis, Scott J.; Demetracopoulos, Constantine A.
Category: Ankle Arthritis Introduction/Purpose: One of the proposed benefits of total ankle replacement, when compared to ankle fusion is the preservation of range of motion (ROM) of the ankle. Preservation of ankle motion may improve quality of life as evidenced by patient-reported outcome measures (PROMs). However, despite improving dorsiflexion intraoperatively during TAR, studies have not demonstrated large improvements in dorsiflexion (DF) at final followup after TAR. The objective of this study was to radiographically evaluate and quantify preoperative, intraoperative ankle dorsiflexion and plantarflexion (PF), compare it to post- operative ankle ROM, and determine the effect of Achilles lengthening (TAL) on preserving dorsiflexion motion that is gained during surgery. Methods: This prospective study compared 111 patients with an average age of 62.3 years who underwent primary total ankle replacement with one of four different implants between March and December 2019. A total of 71 patients (64%) had an associated TAL based on the surgeon's decision. Intraoperative fluoroscopy was utilized by the primary surgeon to document the maximal dorsiflexion and plantar flexion at the end of the case. This was completed after the TAL on a perfect lateral. Standardized weight bearing at maximum ROM positions lateral radiographs were obtained twelve months postoperatively. The change in range of motion was analyzed using a paired t-test with a significance level of 0.05. Results: The cohort's preoperative range was 22.0° (8.1°DF, 14°PF) and was increased to 38.5° intraoperatively (12.7°DF, 25.8°PF) as described in Table 1. Postoperative ROM is 24.9° (11.7°DF, 13.2°PF) which means that 65% of the intraoperative ROM is preserved. Preoperative and intraoperative range of motion was not different between the group that had a TAL compared to no TAL. At the year postoperatively, the dorsiflexion was similar between both groups. The group who did not have a TAL went from 12.8 intraoperatively to 12.2° postoperatively whereas the group who had a TAL went from 12.2° to 11.3° which was statistically equivalent. Conclusion: This study is the first to assess how much ankle range of motion is retained after TAR. Overall, we observed that 65% of dorsiflexion was retained after TAR. TAL as a concomitant procedure did not effect the proportion of dorsiflexion motion that was retained. Additional studies are needed to determine how to best optimize and increase ROM after TAR.